2021
DOI: 10.1108/jhr-10-2020-0478
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful treatment outcome and associated factors among smear-positive pulmonary tuberculosis patients in Kepong district, Kuala Lumpur, Malaysia

Abstract: PurposeThe purpose of this study was to assess tuberculosis (TB) treatment outcomes among new smear-positive pulmonary tuberculosis (PTB) patients and identify the risk factors of unsuccessful treatment outcomes in Kepong district, Kuala Lumpur, Malaysia.Design/methodology/approachA retrospective cohort study was conducted using registry-based data from the Tuberculosis Information System (TBIS) between 2014 and 2018. Simple random sampling was used to select 734 males and 380 females from the TBIS registry. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
4
2
0
Order By: Relevance
“…The present study demonstrated that non-Malaysians had higher odds of having unsuccessful TB treatment outcome, but it was not statistically significant; thus, it was not included as a determinant in this study. This is in concordance with another study performed in Malaysia [ 26 , 28 ]. The small number of non-Malaysian patients with TB-HIV could have contributed to the nonsignificant findings of both studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study demonstrated that non-Malaysians had higher odds of having unsuccessful TB treatment outcome, but it was not statistically significant; thus, it was not included as a determinant in this study. This is in concordance with another study performed in Malaysia [ 26 , 28 ]. The small number of non-Malaysian patients with TB-HIV could have contributed to the nonsignificant findings of both studies.…”
Section: Discussionsupporting
confidence: 93%
“…Here, lack of formal education, being unemployed, and low household income were significantly associated with unsuccessful treatment outcome, compared to having received formal education, being employed, and high household income. These findings are in concordance with other studies that show that people with low socioeconomic backgrounds tend to have a higher risk of poorer TB treatment outcome [ 26 , 35 , 36 ]. The risk of developing TB increases among people with low socioeconomic backgrounds, as they usually live in areas with poor ventilation, have poor knowledge and behavioural practices regarding the disease itself, and are malnourished, which may lead to low immunity [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is often longer and requires more careful monitoring of the course of the disease [10]. The occurrence of relapses is associated with the development of resistance, which dictates the need for strict adherence to the treatment regimen for a first diagnosed tuberculosis process (FDTB) and careful monitoring of the dynamics of the disease to prevent recurrent course [11].…”
Section: Introductionmentioning
confidence: 99%